THE RELATIONSHIP BETWEEN PHYSICAL CONDITIONS OF HOUSE AND SANITATION WITH LEPROSY CASE IN PATIENTS AT SUMBERGLAGAH MOJOKERTO HOSPITAL - Aini Fadlila; Ulfa Nurzila; Retno Adriyani (The Indonesian Journal of Public Health, 2022)
Introduction: The prevalence of leprosy in 2017 in Indonesia shows 6.08 / 100,000 new cases of leprosy and 86.12% of which are multi-bacillary types. Determinants of leprosy events include the condition of residence. The aim of the study is to analyze the relationship between physical condition of house and sanitary facilities with the occurrence of leprosy. Methods: This study uses analytical observational research with a case-control study to analyze the relationship between the physical condition of the house and sanitary facilities and the incidence of leprosy in patients of Sumberglagah Hospital, Mojokerto. The sample size was 38, including 19 cases and 19 controls with simple random sampling. Research variables include individual characteristics, the physical conditions of the home, and sanitary facilities were analyzed using chi-square tests. Result : The results showed there was a significant relationship between physical conditions of house such as the ceiling, the type of floor, humidity, and density of the bedroom (p < α) with leprosy cases. Meanwhile, sanitary facilities do not show a significant relationship with leprosy cases. Conclusion: Efforts to prevent leprosy can be done through education to the public to maintain physical condition of the house according to prevailing requirements, especially the presence of ceilings, type of floor of the house made of materials that are easy to clean, comfortable humidity, and bedrooms not used by more than two people.